PENGARUH PROGRAM PABBAJITA TERHADAP PEMBENTUKAN SIKAP SOSIAL DAN PENINGKATAN PRESTASI AKADEMIK MAHASISWA STAB KERTARAJASA, BATU - Ajar Katono; Sulan; Mettadewi Wong (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Higher education demands a balance between academic achievement and the development of students' social attitudes. The pabbajita program at STAB Kertarajasa is designed to instill values of discipline and self-control through Buddhist spiritual practices. This study aims to explore the extent to which the program influences students’ social attitudes and academic performance. This study employed a quantitative method with a regression design. The research sample consisted of 62 students selected using the Slovin formula. Data collection was conducted through a Likert-scale questionnaire to measure the variables of the pabbajita program and social attitudes, as well as documentation of academic achievement through the Study Result Card (KHS). Data analysis was performed using multiple regression to determine the influence of each variable. The research findings indicate that students’ responses to the pabbajita program reached a percentage score of 76.8%, categorized as strong. Additionally, there was a positive and significant influence of the pabbajita program on social attitudes, with a regression coefficient value of 0.712, an R Square of 0.588, and a significance level of p = 0.000 < 0.05. Meanwhile, the influence on academic achievement was also significant, with a regression coefficient of 0.050, an R Square of 0.063, and a significance level of p = 0.000 < 0.05. It can be concluded that there is a significant influence of the pabbajita program (X1) on social attitudes (Y1) and academic achievement (Y2) simultaneously, with a Sig. value = 0.001 < 0.05. These findings support the idea that the integration of spirituality in higher education can serve as an effective strategy for holistic development of students' character and academic performance.